Neoplastic Lesions of Small and Large Intestine- A Prospective Study in Tertiary Care Hospital - Kalyan Nunna, Venkata; M H, Prabhu; Inamdar, S. S.; Pattanashetti, Mallikarjun; Y, Rachana L (Annals of Pathology and Laboratory Medicine, 2018)
Background: This study was carried out to study the occurrence, evaluate and correlate various histopathologic types of tumors at different sites of gastrointestinal tract in relation to age and sex of the patients operated in Surgery department and specimens received at Pathology department of S.Nijalingappa Medical college, Bagalkot, Karnataka. Methods : A cross sectional histopathological study of gastrointestinal tumors of 45 cases was carried out on surgical specimens and biopsy received from Department of Surgery, S.Nijalingappa Medical College, Bagalkot from January 2016 to July 2017. Specimen were preserved in 10% buffered formalin. It was kept in 10% buffered formalin for proper fixation, subsequently dehydration, clearing, embedding in paraffin wax was carried out. Blocks were made and sections of 3Âµm thickness were cut and stained with Haematoxylin and Eosin stain and slides were reported. Results: : A total of 45 cases were included, among which 26 were males and 19 were females with peak occurrence in sixth decade.The following is anatomical distribution : Small intestine 7(15.5%), Appendix 0(0%), Colon & Rectum 37 (82.2%) and Anal canal 01(2.2%).Histological types seen were - Epithelial 41(91.1%), Mesenchymal 03 (6.6%) and Lymphoma 01(2.2%). Conclusion: Gastrointestinal tumors show a wide variation in the morphology.Hence, histopathological examination is must for the diagnosis and classification of these tumors. The occurrence of gastrointestinal tumors was mostly in the colon and rectum.This study emphasises the need for early diagnosis of the disease through histopathology, which when correlated clinically will help the clinician to implement the appropriate treatment and improve the survival of the patients.